Transformasi Laplace Secara Numerik Menggunakan Interpolasi Hermite dan Spline - Prasetiyo, Ari Puji (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2023)
Laplace transform is a from of integral transform which has many applications in numerous fields. This transform converts a function of a real variable to a function of a complex variable. Function can be found by evaluating the given integral of transform’s definition. In some cases, evaluation of integral of can be too complicated to perform analytically. Then numerical integration is a way out to solve the problems. This paper introduces a simple numerical method of Laplace transform employing composite Simpson rule. Numerical integrations are performed at to construct sequence as approximation of . Hermite and spline interpolation is the applied to in order to produce as the numerical Laplace transform of . The accuracy of the proposed method is revealed by calculating the distance between and using norm. As the results, function can provide a decent approximation of for some test functions. In general, Hermite interpolation produces which is closer to compared to the result obtained by spline interpolation.